The effect of tree-on-tree interactions and abiotic conditions on woody communities in Brazilian savannas - Chagas, Davi Borges; Rapini, Alessandro; Villa, Pedro Manuel; Collevatti, Rosane Garcia [UNESP] (Cambridge University Press (CUP), 2023)
Fire plays a crucial role in shaping plant communities in South American savannas. However, the impact of biotic interactions on tree communities still needs to be better explored. In this study, we evaluated the influence of tree-on-tree interactions and abiotic conditions on the structure and diversity of woody communities in savannas of Central Brazil. We used plots of 10 × 10 m in three preservation areas of savanna to assess the abundance and composition of juveniles and adults in woody communities associated with two Apocynaceae tree species: Hancornia speciosa, postulated to show negative interactions with the associated tree community, and Himatanthus obovatus, postulated to show positive interactions. Our results revealed that while abiotic factors, represented by the altitude, are more critical in shaping the community of juvenile trees, tree-on-tree interactions have a stronger influence on adult tree populations, driving community dynamics during plant recruitment. Specifically, Hancornia speciosa reduces the abundance of adults, whereas Himatanthus obovatus enhances their relative abundance; both shape the composition of tree communities. Consequently, tree-on-tree interactions create distinct mosaics at various stages of regeneration, contributing to savanna dynamics and conservation.
Keywords: Beta diversity; biotic interactions; Cerrado; ecological structure; plant community; recruitment; regeneration